Medication Adherence and Common Barriers for Caregivers of Preschool Children with Pediatric Glaucoma - Zitian Liu; Yuning Zhang; Pingping Liu; Wenxin Yang; Xinyan Li; Yimin Zhong; Yangfan Yang; Xing Liu; Huiming Xiao; Minbin Yu; Wenmin Huang (Journal of Ophthalmology)
Purpose. To investigate the medication adherence among caregivers of preschool children with pediatric glaucoma and to elucidate common barriers leading to poor adherence. Methods. A cross-sectional study. Caregivers of preschool children with pediatric glaucoma completed a questionnaire on demographic information of caregivers, demographic and disease characteristics of children, caregivers-reported medication adherence (by an adapted Morisky Adherence Scale), and possible 13 barriers. Results. Overall 132 questionnaires were considered valid. Thirty-six percent of all reported poor medication adherence. Caregivers’ age and self-evaluated knowledge about pediatric glaucoma showed a significant difference between the adherent and nonadherent groups (P<0.05). Nineteen percent of all reported only one barrier as important, 65% cited multiple barriers, and 16% cited no barriers. Anxiety and depression were cited as important by most caregivers in both groups. Univariate logistic regression analysis demonstrated that difficulty with the acquisition of medications (OR, 2.5; 95% CI, 1.1–5.7; P=0.025), difficulty with medication schedule (OR, 2.3; 95% CI, 1.0–5.0; P=0.043), and high expenses for medications (OR, 4.8; 95% CI, 1.4–15.9; P=0.011) were significantly associated with higher odds of poor adherence. Conclusions. Over one-third of caregivers of preschool children with pediatric glaucoma were in poor medication adherence. Nearly two-thirds of caregivers cited multiple barriers simultaneously as important hindrances to medication usage. Anxiety and depression, difficulty with the acquisition of medications, difficulty with the medication schedule, and high expenses for medications were prominent barriers. Individualized solutions should be provided according to reported barriers by each caregiver and the other most common barriers.